TANGGUNG JAWAB HUKUM PERUSAHAAN OVER THE TOP DALAM PERSAINGAN USAHA TELEKOMUNIKASI DI INDONESIA - Hugo Prathama; Rasji Rasji (Jurnal Hukum Adigama, 2022)
The use of over-the-top (OTT)-based communication services does have several advantages,including that there is no charge for communicating, compared to making a communicationthrough a provider network which can be charged. The problem faced is whether there is a needfor legal equalization of OTT companies in the telecommunications sector withtelecommunications service providers in Indonesia? and what are the legal responsibilities of OTTcompanies in the telecommunications business competition in Indonesia? The research methodused is a normative juridical legal research method. The results show that the legal equivalent ofOTT companies is that the government requires global OTT cooperation with national operatorsunder a legal umbrella, the establishment of BUT is based on the provisions of laws andregulations in the field of taxation, and local and foreign companies pay taxes. The legalresponsibilities of OTT companies in telecommunication business competition in Indonesia are toprovide services and comply with the provisions of laws and regulations in the fields of prohibitionof monopolistic practices and unfair business competition, trade, consumer protection, intellectualproperty rights, broadcasting, film, advertising, pornography, anti-terrorism, taxation; and theprovisions of other relevant laws and regulations. There is a need for regulations for OTT not onlyfor the benefit of local OTT, but for the Unitary State of the Republic of Indonesia.